Review of Epidemiological Study of Nepal Demographic and Health Survey (NDHS) 2006, 2011 and 2016 (TUTA Journal, 2022)
The article aims to explore the comparative epidemiological review of three DHS of Nepal from i.e. 2006, 2011 and 2016 in terms of the basic background of the surveys, their objectives, sampling design, questionnaire design, data collection procedure as well as data processing of the DHS. This review helps for comparability of epidemiological survey designs on the key themes of socio-economic, demographic and health related issues to understand trends over time. The 2006 NDHS had applied only filled out data in paper questionnaire. But 2011 NDHS onward, tablet was used and filled out questionnaire was sent through internet to mail the questionnaire. Level of anemia among women 15-49 and among children 6-59 months was measured first time in 2006 NDHS. Domestic violence was a separate section in 2016 NDHS. Verbal autopsy for causes of under-five mortality was administered in 2006 and 2016 to all women age 15-49 for getting information on still birth and death of under five children during five year preceding the survey. As drawbacks, non-communicable diseases, injuries and some major communicable diseases are inadequately covered in the NDHS. HIV/AIDS was not measured even in the latest DHS. Most of the demographic and health indicators have been improved significantly over time.